2020
DOI: 10.1007/s00540-020-02837-0
|View full text |Cite
|
Sign up to set email alerts
|

Unique challenges in pediatric anesthesia created by COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) has affected anesthetic care worldwide, including the provision of anesthesia for pediatric patients. Hospitals have balanced the risks associated with the potential surges of resource-intensive COVID-19 patients against the probable morbidity of delaying elective surgical procedures. These decisions are complicated by the unclear influence that COVID-19 has on the perioperative risk for disease-positive pediatric patients. We conducted a comprehensive literature search on M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 37 publications
3
26
0
1
Order By: Relevance
“…A review of children with COVID‐19 who had a general anaesthetic reported one peri‐operative death in nine symptomatic cases [ 3 ]. Studies have reported anaesthesia‐related complications in adults with COVID‐19 [ 3 , 4 , 5 ].…”
mentioning
confidence: 99%
“…A review of children with COVID‐19 who had a general anaesthetic reported one peri‐operative death in nine symptomatic cases [ 3 ]. Studies have reported anaesthesia‐related complications in adults with COVID‐19 [ 3 , 4 , 5 ].…”
mentioning
confidence: 99%
“…Perioperative concerns for surgery in such cases are false-negative RT-PCR in children, low yield of viral ribonucleic acid (RNA) from nasopharyngeal samples, nonspecific symptomatology, risk of perioperative viral aerosolization, postviral reactive airway with critical respiratory events during extubation, unexpected postop ventilation, and myocarditis (38-50%). [5][6][7] Data on clinical outcomes in pediatric patients with COVID-19 undergoing emergency surgery is sketchy and mostly extrapolated from adult studies. [5][6][7] This was a multidisciplinary effort involving cardiac-and neuroanesthesiologists and cardiac and neurosurgeons with perioperative intensive care management for successful outcome.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Data on clinical outcomes in pediatric patients with COVID-19 undergoing emergency surgery is sketchy and mostly extrapolated from adult studies. [5][6][7] This was a multidisciplinary effort involving cardiac-and neuroanesthesiologists and cardiac and neurosurgeons with perioperative intensive care management for successful outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anaesthesiologists need to be aware of children specific problems and their management e.g., avoiding nasal premedication since it can cause aerosolisation. [ 11 ] In addition, anaesthesia management by a paediatric anaesthesiologist will enable safe and quick performance of routine tasks like intubation as well as complex tasks like placement of invasive lines and nerve blocks. A generalist is more likely to struggle and take extra time for performance of these practical tasks thereby increasing the possibility of aerosol generation.…”
Section: Introductionmentioning
confidence: 99%